Uniformity Masks Design Method Based on the Shadow Matrix for Coating Materials with Different Condensation Characteristics - Lichao Zhang; Xikun Cai (The Scientific World Journal)
An intuitionistic method is proposed to design shadow masks to achieve thickness profile control for evaporation coating processes. The proposed method is based on the concept of the shadow matrix, which is a matrix that contains coefficients that build quantitive relations between shape parameters of masks and shadow quantities of substrate directly. By using the shadow matrix, shape parameters of shadow masks could be derived simply by solving a matrix equation. Verification experiments were performed on a special case where coating materials have different condensation characteristics. By using the designed mask pair with complementary shapes, thickness uniformities of better than 98% are demonstrated for MgF2 () and LaF3 () simultaneously on a 280 mm diameter spherical substrate with the radius curvature of 200 mm.